2008
DOI: 10.1142/s0219877008001382
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Ambiguity in New Product Development

Abstract: In this paper we challenge the traditional notion of ambiguity as an undesirable element in New Product Development (NPD) and explore how companies sometimes sustain or even increase ambiguity during their NPD projects. Based on qualitative analysis of case data from four NPD projects in the medical-device industry, we present a model by which this process can be better understood. We identify four ways that NPD projects can benefit from temporarily sustaining ambiguity: retaining fallback options, saving cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…A common, and often unstated, assumption in the product development literature is that uncertainty and ambiguity should be reduced as quickly and efficiently as possible, but this assumption is so simplistic as to be misleading. Our assumption here is that ambiguity can be beneficial [6] [15] [46] [47]. In fact, some thrive in the face of ambiguity, perceiving it as desirable, interesting and challenging [18].…”
Section: Ambiguity and Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…A common, and often unstated, assumption in the product development literature is that uncertainty and ambiguity should be reduced as quickly and efficiently as possible, but this assumption is so simplistic as to be misleading. Our assumption here is that ambiguity can be beneficial [6] [15] [46] [47]. In fact, some thrive in the face of ambiguity, perceiving it as desirable, interesting and challenging [18].…”
Section: Ambiguity and Searchmentioning
confidence: 99%
“…A series of ethnographic studies of innovation efforts in the medical technology industry found that outcomes tended to vary-at least in part-dependent on how innovation teams tolerated ambiguity [4] [5] [6] [7] [46] [47]. In one example, a small team embracing ambiguity and divergent interpretations of a cue led to outcomes that were initially likely to be rejected, but ultimately proved highly successful.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of its focus on maximization of value, seeking clear de¯nitions of alternatives and predetermined decision criteria [Christiansen and Varnes (2008); Stilling and Eskerod (2008); Brun et al (2009)]. It is assumed that decisions lead to actions that are consistent with the objectives of the decision.…”
Section: A Critical View Of Ppm Literaturementioning
confidence: 99%
“…However, ambiguous situations, in which people experience confusion or con°icting interpretations when evaluating ideas, have not been thoroughly addressed in PPM literature [Bergman et al (2007); Brun et al (2008Brun et al ( , 2009Engwall et al (2003); Verganti (2011)]. …”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation